Hubungan Pola Kebiasaan Makan Dengan Terjadinya Karies Gigi Pada Anak - Mutiara Rina Rahmawati Ruslan; Pindobilowo (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2016)
Background: The prevalence of dental caries among children remains high. This condition may well be linked to improper dietary habits, society behavior and children’s frequent consumption of cariogenic foods that cause dental caries. Purpose: The purpose of the study is to find the relevance of dietary habits towards the occurrence of dental caries among kindergarten aged children and is used as a point of reference for UKGS (School Dental Health Service) on early prevention program of tooth decay. Materials and Methods: A cross sectional study of 130 children was carried out in three kindergartens within UPDM (B) Dentistry area. Clinical examination on children, questionnaire, parents’ interview and purposive sampling technique were undertaken. Employing chi square test by using a dependent variable of caries in children and independent variables such as: age (p=0.000), gender (p=0.035), plaque pH (p=0.007), type of foods (p=0.012), frequency of eating (p=0.000), meals (p=0.000), parent education (p=0.174) and family income (0.835). Result: It is evident that there is a significant link between age, gender, pH plaque, food types, number of meals, meals time with caries. Caries prevalence was 78. 5%, def-t at 6.09.